The Modulating Effect of Glucocorticoids and Opioid System on Anxiety Related Behavior in Young and Adult Rats: Economic Evaluation of Infliximab in UC Patients - Mahnaz Kesmati; Maryam Rezai; Mozhgan Torabi (Iranian Journal of Pharmaceutical Sciences, 2016)
One of the main components of the stress system is hypothalamus- pituitary-adrenal (HPA) axis. Acute activation of μ-opioid receptors increases the activity of the HPA axis, leading to release of ACTH and corticosterone. Glucocorticoids can change behaviors, depend on age but there were no evidences about the interaction between age, opioid system and glucocorticoids. In this experiment, effects of dexamethasone (1mg/kg) and RU486 (20mg/kg) as an agonist and antagonist of glucocorticoid receptors, morphine (5mg/kg) and naloxone (20mg/kg) as an agonist and antagonist of the opioid system on anxiety in young and adult male Wistar rats were examined. The percentage of time in the open arms of plus maze was evaluated for anxiety behavior also percentage of the number of entries in closed arms was evaluated for locomotor activity. The results showed that morphine (5mg/kg) and dexamethasone (1mg/kg) had an anxiolytic effect on both young and adult rats while just in young rats reduced locomotor activity. RU486 could prevent the anxiolytic effect of morphine, and the anxiolytic effect of dexamethasone had been inhibited by naloxone in young but it wasn’t seen in adult rats. These results show an interactive effect between glucocorticoids and the opioid system on mediating anxiety that can be influenced by age.